1978
DOI: 10.1039/p19780000163
|View full text |Cite
|
Sign up to set email alerts
|

18-Norpregna-8,11,13-trienes. Part 2. Preparation from 17β-methyl-17α-pregn-13-enes

Abstract: 5~-androsta-8,11 ,I 3-trien-3a-yl acetate (6) has been prepared from 9a.11 a-epoxy-l7amethyl-5(3-androstane-3a,l7(3-diol 3-acetate (5) in good yield. An attempt to repeat the aromatisation with the analogous 9a.11 cc-epoxy-5P-pregnane-3a,l7a,20P-triol 3,20-diacetate (1 0) did not give the expected product. However, a number of ring-c-aromatic pregnanes have been successfully prepared from derivatives of 5P-pregnane-3a.11 p.17a, . Attempts to aminate some of these aromatic pregnanes a t the 3-and 20-positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…8 However, the synthesis of tetronic acids involving various starting materials with multi-step synthetic routes under harsh reaction conditions has been explored previously. [82][83][84][85] T. Yamada et al first reported the synthesis of tetronic acids using CO 2 fixation in conjugate ynone. 86 However, the synthesis of the starting conjugate ynone substrate in this procedure is quite difficult and produces unwanted side products.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, the synthesis of tetronic acids involving various starting materials with multi-step synthetic routes under harsh reaction conditions has been explored previously. [82][83][84][85] T. Yamada et al first reported the synthesis of tetronic acids using CO 2 fixation in conjugate ynone. 86 However, the synthesis of the starting conjugate ynone substrate in this procedure is quite difficult and produces unwanted side products.…”
Section: Introductionmentioning
confidence: 99%